Vitamin D counteracts fibrogenic TGF-β signalling in human hepatic stellate cells both receptor-dependently and independently. Issue 5 (18th August 2014) - Beilfuss, Anja; Sowa, Jan-Peter; Sydor, Svenja; Beste, Mechthild; Bechmann, Lars P; Schlattjan, Martin; Syn, Wing-Kin; Wedemeyer, Inga; Mathé, Zoltan; Jochum, Christoph; Gerken, Guido; Gieseler, Robert K; et al.
Abstract : Objective: Non-alcoholic fatty liver disease (NAFLD) is closely linked to obesity and constitutes part of the metabolic syndrome, which have been associated with low serum vitamin D (VD). Due to known crosstalk between VD and transforming growth factor (TGF)-β signalling, VD has been proposed as an antifibrotic treatment. Design: We evaluated the association between VD, the vitamin D receptor (VDR) and liver fibrosis in primary human hepatic stellate cells (phHSC) and 106 morbidly obese patients with NAFLD. Results: Treating phHSC with VD ameliorated TGF-β-induced fibrogenesis via both VDR-dependent and VDR-independent mechanisms. Reduction of fibrogenic response was abolished in cells homozygous for GG at the A1012G single nucleotide polymorphisms within the VDR gene. Compared with healthy livers, NAFLD livers expressed higher levels of VDR mRNA and VDR fragments. VDR mRNA was lower in patients homozygous for GG at A1012G and expression of pro-fibrogenic genes was higher in patients carrying the G allele. Conclusions: VD may be an antifibrotic treatment option early in the onset of fibrosis in specific genotypes for VDR. Known polymorphisms of the VDR may influence the response to VD treatment.